Association between Leave Provisions and Job Satisfaction: A Study on Commercial Banks of Bangladesh - Omar Faroque,; Rahman, Md. Sahidur; Rahman, Mostafizur (Society & Sustainability, 2020)
This study aims to determine the relationships between leaves and job satisfaction among the employees of some commercial banks in Bangladesh. Data on selected leaves and job satisfaction related factors have been collected through survey method from mid-level and entry-level employees of 29 private commercial banks in Bangladesh. The respondents were selected through convenient sampling. Frequency distribution has been utilized to explore the leaves and job satisfaction related characteristics of the respondents. Chi-square test and binary logistic regression analysis were employed to test the hypotheses and to estimate the existing relationships among the variables. The chi-square test reveals that marital status, education, weekly holidays, causal, sick and earned leaves, festival holidays and parental leaves are strongly associated with job satisfaction. The logistic analysis shows that marital status, education, weekly holidays, casual leaves, festival holidays and parental leave have significant relationships with job satisfaction. There is a 88% association between leaves and job satisfaction of the employees at different commercial banks of Bangladesh. The findings imply that organization policy regarding festival holidays, parental leaves, weekly holidays, and casual leaves has a vital role in the job satisfaction of the employees.